Oxovanadium(IV) and dioxouranium(VI) complexes with nucleic acid bases - Ghose R. (My University, 2025)
Simple and mixed ligand oxovanadium(IV) and dioxouraniura(VI) complexes with adenine and uracil as well as with,adenine and thymine have been synthesized. The new complexes were characterised by elemental analyses. Spectral studies suggest that adenine is coordinated to the metal ions through the N(7) and N(9) atoms. Uracil is coordinated through the C4=O group while thymine through its C2=O group to the metal ions. The complexes involving adenine are polymeric in nature with adenine bridges between metal ions. The oxovanadium(IV) complexes exhibit the coordination number five and the dioxouranium(VI) complexes the coordination number six. Powder X-ray diffraction studies indicate orthorhombic symmetry for the oxovanacium(IV) and tetragonal symmetry for the dioxouranium(VI) mixed ligand complexes.